Portfolio assessment in the frame of multi-layered peer coaching: An alternative portfolio for pre-service teachers - Siti Tarwiyah; Nuna Mustikawati Dewi; Fatah Syukur (EduLite: Journal of English Education, Literature and Culture, 2021)
Literature has shown that portfolio assessment is meaningful for supporting student-teachers’ language and teaching skills. However, integrating portfolio assessment and Multi-layered Peer Coaching (MPC) is still scarcely done. To fill in this empirical void, this study elaborates the implementation of portfolio assessment in Micro Teaching class integrated with MPC. This is a case study with 22 pre-service teachers and one teacher educator as data sources. The data were collected through observation and documentation, and analyzed by using interactive model of analysis. It reveals that the artifacts of portfolio are dominated by collaboration-based products, comprising 13 artefacts. This portfolio may be developed to accommodate alternative assessment in Micro Teaching Class.